2022
DOI: 10.1016/j.ymthe.2022.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Synapsin III gene silencing redeems alpha-synuclein transgenic mice from Parkinson's disease-like phenotype

Abstract: Fibrillary aggregated a-synuclein (a-syn) deposition in Lewy bodies (LB) characterizes Parkinson's disease (PD) and is believed to trigger dopaminergic synaptic failure and a retrograde terminal-to-cell body neuronal degeneration. We described that the neuronal phosphoprotein synapsin III (Syn III) cooperates with a-syn to regulate dopamine (DA) release and can be found in the insoluble a-syn fibrils composing LB. Moreover, we showed that a-syn aggregates deposition, and the associated onset of synaptic defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Using an aggregation specific α-syn antibody, we confirmed that the observed puncta in the striatum were in fact α-syn aggregates. Increasing evidence suggests aggregation of α-syn at the synapse is an early event in PD pathogenesis and is associated with impaired striatal synaptic function and DA neuronal death ( Faustini et al, 2022 ; Srinivasan et al, 2021 ). While PD patients with Parkin mutations rarely exhibit Lewy pathology ( Schneider and Alcalay, 2017 ), only seventeen studies published from 1994 to 2018 have investigated post-mortem brains from such patients with a focus on Lewy body formation and of these eight reported the presence of Lewy bodies and one showed basophilic Lewy body-like inclusion bodies (reviewed in ( Madsen et al, 2021 )).…”
Section: Discussionmentioning
confidence: 99%
“…Using an aggregation specific α-syn antibody, we confirmed that the observed puncta in the striatum were in fact α-syn aggregates. Increasing evidence suggests aggregation of α-syn at the synapse is an early event in PD pathogenesis and is associated with impaired striatal synaptic function and DA neuronal death ( Faustini et al, 2022 ; Srinivasan et al, 2021 ). While PD patients with Parkin mutations rarely exhibit Lewy pathology ( Schneider and Alcalay, 2017 ), only seventeen studies published from 1994 to 2018 have investigated post-mortem brains from such patients with a focus on Lewy body formation and of these eight reported the presence of Lewy bodies and one showed basophilic Lewy body-like inclusion bodies (reviewed in ( Madsen et al, 2021 )).…”
Section: Discussionmentioning
confidence: 99%
“…First, it facilitates the formation of the SNARE complex, which is essential to neurons as it regulates the fusion of synaptic vesicles to the plasma membrane, leading to neurotransmitter release (Sudhof 2013 ). Second, it regulates neurotransmitter release by restricting synaptic vesicle mobilization and recycling (Faustini et al 2022 ). However, the interplay between the synaptic vesicle release machinery and pathological α-syn remains poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…At present, our knowledge of the features of aSyn micro‐aggregates, their trans‐synaptic spreading potential or intrinsic toxicity in PD or DLB is still scarce, but it is likely that their progressive accumulation in the few spared neurons, rather than LB formation, represents the noxious event contributing to neurodegeneration and disease progression. Along these lines, recent reports showed that genetic‐based control of the expression of αSyn synaptic protein partners in the brain of human αSyn transgenic mice at a pathological stage could halt neurodegeneration and restore dopaminergic neuron function and animal motility by reducing the deposition of fibrillary αSyn 50,51 . This suggests that the αSyn fibrils forming microaggregates may constitute a more dynamic and possibly reversible entity than those forming mature LB, because they are destabilized by changes in the αSyn interactome.…”
Section: Gaps and Controversiesmentioning
confidence: 99%
“…Along these lines, recent reports showed that genetic-based control of the expression of αSyn synaptic protein partners in the brain of human αSyn transgenic mice at a pathological stage could halt neurodegeneration and restore dopaminergic neuron function and animal motility by reducing the deposition of fibrillary αSyn. 50,51 This suggests that the αSyn fibrils forming microaggregates may constitute a more dynamic and possibly reversible entity than those forming mature LB, because they are destabilized by changes in the αSyn interactome. Therefore, it may also be easier to clear them from the brain.…”
Section: Gaps and Controversies Is Accumulation Of Protein Aggregates...mentioning
confidence: 99%